Sex-specific regulation of IL-10 production in human adipose tissue in obesity - Subramanian, Narmadha; Tavira, Beatriz; Hofwimmer, Kaisa; Gutsmann, Beate; Massier, Lucas; Abildgaard, Julie; Juul, Anders; Rydén, Mikael; Arner, Peter; Laurencikiene, Jurga (Frontiers in Endocrinology, 2022)
Background: Obesity-associated metabolic complications display sexual dimorphism and can be impacted by cytokines. We previously showed that interleukin-10 (IL-10) was upregulated in white adipose tissue (WAT) of obese women with type 2 diabetes (T2D). Whether this pertains to men is unknown. The aim of this study was to compare the impact of obesity and T2D on WAT IL-10 levels in men versus women. Methods: Plasma and subcutaneous WAT biopsies were obtained from 108 metabolically well-characterized individuals. WAT IL10 expression/secretion and WAT-resident IL-10-secreting macrophage number were measured. Circulating sex hormone levels were correlated to WAT IL10 expression in 22 individuals and sex hormone effects on macrophage IL10 expression were investigated in vitro. Results: Obese women with T2D showed increased IL10 expression/secretion and IL-10-secreting WAT macrophage number compared to other female groups. This difference was absent in men. Non-obese women and men with T2D showed similar IL-10 levels compared to healthy controls, indicating that T2D alone does not regulate IL-10. Although WAT IL10 expression correlated with serum estrone (E1) concentrations, recombinant E1 did not affect macrophage IL10 expression in vitro. Conclusion: WAT IL-10 levels are higher in women with obesity and T2D, but not in men and this effect is primarily attributed to obesity per se. This is less likely to be driven by circulating sex hormones. We propose that the WAT IL-10 might exert protective effects in obesity-associated chronic inflammation in women which could be one of the contributing factors for the decreased morbidity observed in women during obesity than men.